Modified constrained adaptive formation control scheme for autonomous underwater vehicles under communication delays. Issue 1 (15th January 2021) - Suryendu, Chhavi; Subudhi, Bidyadhar
Abstract : The performance of a formation control algorithm for a group of autonomous underwater vehicles (AUVs) may be degraded due to communication constraints between the leader and the follower AUVs. Moreover, as the distance between the AUVs change due to ocean waves, the delay in communication also varies. In this study, a modified constrained adaptive controller (CAC) is proposed to resolve the issue of variable‐delay as well as actuator saturation. Due to the on‐line reduction of the cost function, the gains of the CAC are updated at each sampling time taking into account the effects of communication delay. This improves the path‐following accuracy of the leader AUV as well as follower AUVs. The effectiveness of the proposed control algorithm is demonstrated by implementing it on a prototype AUV (ODRA‐I) model. The obtained simulation and experimental results show that the follower AUVs maintain a desired distance from the leader AUV to avoid a collision. For the proposed algorithm, the desired path‐following performance of the follower AUV is maintained even when the delay is changed from 0 to 5 s. Moreover, the proposed control algorithm is efficient in avoiding actuator saturation.